An updated geothermal model of the Dutch subsurface based on inversion of temperature data. (November 2020) - Békési, Eszter; Struijk, Maartje; Bonté, Damien; Veldkamp, Hans; Limberger, Jon; Fokker, Peter A.; Vrijlandt, Mark; van Wees, Jan-Diederik
Highlights: 3D subsurface thermal model of the onshore Netherlands. Conductive heat transport. Pseudo-convective approach to approximate hydrothermal convection. Data assimilation using temperature measurements as observations. Abstract: The subsurface temperature is one of the most crucial parameters for the development of geothermal energy. Physics-based temperature models calibrated with temperature data are especially relevant for deep geothermal exploration. We present an updated high-resolution 3D thermal model of the onshore Netherlands. We constructed the model in 7 steps, starting from a lithospheric-scale, physics-based forward model and progressively detailing and updating it using temperature data. The model is built up from 14 sedimentary layers and layers for the upper crust, lower crust, and lithospheric mantle. We assigned a-priori thermal properties for each layer and updated them through an inversion procedure by the Ensemble Smoother with Multiple Data Assimilation (ES-MDA), using 1507 temperature measurements as observations. Misfits of the prior model are significantly reduced through the data assimilation procedure, demonstrating the effectiveness of ES-MDA as a tool for calibrating temperature models, supporting high-resolution external constraints. The resulting posterior model describes the thermal state in the uppermost 10 km of the Netherlands with a horizontal resolution of 1 km, a vertical resolution of 200 m, and an overall RMS misfit of 0.7 °C. The thermal state of the deep subsurface is important for geothermal exploration that targets the deeply buried Devonian-Carboniferous carbonate formations in the Netherlands. These reservoirs are potentially suitable for industrial heating applications and electricity production. To this end, one of the main aspects of this study was to incorporate the thermal effect of hydrothermal convection within the Dinantian carbonate platforms, following the example found in the Luttelgeest-01 (LTG-01) well. Our model reveals areas in the Netherlands with potential for convection in these carbonate platforms, highlighting locations that can be suitable for deep geothermal development.